Care and the City Encounters with Urban Studies - Gabauer, Angelika; Knierbein, Sabine; Cohen, Nir; Lebuhn, Henrik; Trogal, Kim; Viderman, Tihomir; Haas, Tigran (Taylor & Francis, 2022)
Care and the City is a cross-disciplinary collection of chapters examining urban social spaces, in which caring and uncaring practices intersect and shape people's everyday lives. While asking how care and uncare are embedded in the urban condition, the book focuses on inequalities in caring relations and the ways they are acknowledged, reproduced, and overcome in various spaces, discourses, and practices. This book provides a pathway for urban scholars to start engaging with approaches to conceptualize care in the city through a critical-reflexive analysis of processes of urbanization. It pursues a systematic integration of empirical, methodological, theoretical, and ethical approaches to care in urban studies, while overcoming a crisis-centered reading of care and the related ambivalences in care debates, practices, and spaces. These strands are elaborated via a conceptual framework of care and situated within broader theoretical debates on cities, urbanization, and urban development with detailed case studies from Europe, the Americas, and Asia. By establishing links to various fields of knowledge, this book seeks to systematically introduce debates on care to the interconnecting fields of urban studies, planning theory, and related disciplines for the first time.